2013
DOI: 10.1038/srep01270
|View full text |Cite
|
Sign up to set email alerts
|

Defect mediated manipulation of nanoclusters on an insulator

Abstract: With modern scanning probe microscopes, it is possible to manipulate surface structures even at the atomic level. However, manipulation of nanoscale objects such as clusters is often more relevant and also more challenging due to the complicated interactions between the surface, cluster and apparatus. We demonstrate the manipulation of nanometer scale gold clusters on the NaCl(001) surface with a non-contact atomic force microscope, and show that the movement of clusters is in certain cases constrained to spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 58 publications
(68 reference statements)
0
11
0
Order By: Relevance
“…Such experiments could be further assisted by Kelvin probe microscopy33, which has shown to be quite powerful for measuring, e.g., work function differences at the nanometer34 and even atomic scale35. Most importantly, since STM as well as nc-AFM nowadays allow manipulating atoms36, molecules37 and clusters38, the two types of microscopes could be used, in principle, to manipulate the second layer silicene islands on the first one, provided that the coupling between the layers is only weak. Note that the manipulation of thin films has been exemplified by recent experiments of NaCl films on Cu(111)39.…”
Section: Discussionmentioning
confidence: 99%
“…Such experiments could be further assisted by Kelvin probe microscopy33, which has shown to be quite powerful for measuring, e.g., work function differences at the nanometer34 and even atomic scale35. Most importantly, since STM as well as nc-AFM nowadays allow manipulating atoms36, molecules37 and clusters38, the two types of microscopes could be used, in principle, to manipulate the second layer silicene islands on the first one, provided that the coupling between the layers is only weak. Note that the manipulation of thin films has been exemplified by recent experiments of NaCl films on Cu(111)39.…”
Section: Discussionmentioning
confidence: 99%
“…In this state, considering the amount of indentation, the contact is divided into two sections. If 1 0 C 0 6, the relationships between the dimensionless contact load and the dimensionless interference, and between the dimensionless contact area and the dimensionless interference, are shown by equations (4) and 5, respectively.…”
Section: Elastic Rangementioning
confidence: 99%
“…Hynninen et al investigated these challenges to direct the manipulation of a nanocluster beyond the constraint of the tip's scanning direction. 4 Korayem et al studied the simulation of cylindrical and capped cylindrical micro/nanoparticle contact. They concluded that the indentation depth of capped cylindrical particles is less than that of spherical particles and larger than cylindrical particles.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, atomic force microscopy (AFM), as a viable alternative, has been used to provide atomic-scale images of surfaces, characterize atoms and molecules, [17][18][19] and manipulate the nanoclusters. 20,21 In contrast to STM, AFM can avoid the unintended charge rearrangement due to its force modulation mechanism. 17 Moreover, Kelvin probe force microscopy (KPFM) due to its atomic scale precision allows us to directly detect the different charge states within the atomic scale using the local contact potential difference (LCPD).…”
Section: Introductionmentioning
confidence: 99%